Eviction and crime: a neighborhood analysis in Philadelphia - Semenza, Daniel C. (Crime & delinquency, 2022)
In this study, we use generalized estimating equation (GEE) models to analyze how rates of eviction correspond to homicide, robbery, and burglary rates across all residential neighborhoods in Philadelphia from 2006 through 2016. We assess the moderating role of neighborhood poverty accounting for residential mobility, economic disadvantage, and community composition. We find that eviction is associated with all three types of crime in fully controlled models. Additionally, neighborhood poverty significantly moderates this relationship for robbery and burglary, but not homicide. We discuss the implications of these results with attention to policy opportunities to reduce eviction and suggestions for future research.